Linking intangible resources and entrepreneurial orientation to export performance: The mediating effect of dynamic capabilities - Albertina Paula Monteiro; Ana Maria Soares; Orlando Manuel Martins Marques de Lima Rua (Journal of Innovation & Knowledge (JIK), 2019)
This study investigates the effect of intangible resources and entrepreneurial orientation in export performance, by examining the mediating effect of dynamic capabilities. A framework of export antecedents is developed and empirically tested. A survey of 265 Portuguese exporting companies shows that dynamic capabilities and entrepreneurial orientation directly impact export performance while financial, informational and relational resources have an indirect impact in export performance through dynamic capabilities. These results point to the important role of dynamic capabilities, sheding light on how intangible resources can be used by companies to enhance export performance, highlighting also the role of entrepreneurial orientation to leverage business' export performance. Our findings have relevant theoretical implications. For the Dynamic Capabilities View (DCV) literature, given the support for the impact of dynamic capabilities in performance by leveraging the impact of resources, and for the entrepreneurship literature, given the finding that entrepreneurial orientation potentiates export performance. More importantly, our study provides support for these relationships in the context of international markets. Practical implications for export supporting policies are also noted.
Keywords: M10; M16; M19; M20; M29; 650; Dynamic capabilities; Entrepreneurial orientation; Export performance; Intangible resources; SEM